Study on the Influence Mechanism of Surface Morphology on Wear and Thermal Fatigue Performance of Laser-Treated Bionic Brake Drum - Wei Liu; Haiyang Yang; Yuqing Zhou; Ti Zhou; Huijun Xie (Metals)
This study explores the mechanisms underlying the enhanced anti-wear and thermal fatigue performance of laser-treated bionic brake drums, aiming to extend their service life and improve design quality. Bionic brake drums treated with laser patterns—point, stripe, and grid—were tested with semi-metallic, non-asbestos organic (NAO), and ceramic brake pads. A mechanical model was developed to analyze wear performance, and bench tests were conducted to assess wear patterns. Thermal fatigue tests examined the impact of thermal cycling on the treated drums’ wear behavior. The results reveal that laser-treated bionic brake drums significantly outperformed untreated ones in both wear resistance and thermal fatigue. Among the treatments, the grid pattern showed the best wear performance, and thermal fatigue life was improved by 27% for the striped pattern and 38% for the grid pattern. The study concludes that laser treatment effectively enhances both wear resistance and thermal fatigue performance in bionic brake drums, especially for the grid pattern, offering valuable insights for future brake drum design.